Cycloastragenol in inflammation-related diseases: mechanisms, pharmacokinetics, and translational prospects - Zhao, Chun; Yang, Xiuhua; Yao, Man; Song, Xiaoxuan; Dai, Jingtong; He, Pilong (Frontiers in Pharmacology, 2026)
Chronic inflammation, driven by dysregulated immune responses and oxidative stress, underlies the pathogenesis of numerous diseases, from neurodegeneration to cancer. Cycloastragenol (CAG), a bioactive triterpenoid derived from Astragalus membranaceus, has emerged as a multifaceted therapeutic candidate due to its unique ability to simultaneously modulate inflammatory signaling networks, while exhibiting a favorable safety profile in preclinical models. This study aims to systematically evaluate the molecular mechanisms of CAG, including its coordinated anti-inflammatory, immune-regulatory, and tissue-protective effects. By integrating evidence from pharmacology, metabolomics, and clinical studies, our aim is to elucidate the therapeutic potential of CAG and identify strategies to overcome its pharmacokinetic limitations for clinical translation. A comprehensive literature review was conducted using databases such as PubMed, Web of Science, and Science Direct, employing target keywords related to cycloastragenol, inflammation, and disease treatment. Our analysis reveals that CAG exerts multidimensional and networked anti-inflammatory effects by synergistically regulating key inflammatory nodes such as NF-κB, Nrf2, and the NLRP3 inflammasome, as well as by alleviating oxidative stress. It has demonstrated therapeutic potential in diseases such as cancer, neurological disorders, asthma, and visceral fibrosis. CAG exerts significant anti-inflammatory effects by targeting the axis associated with inflammation, oxidative stress, and immune dysregulation. However, future efforts need to focus on improving its bioavailability and verifying its safety in human trials to develop a new generation of anti-inflammatory therapies.